2019
DOI: 10.1001/jamanetworkopen.2018.7754
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thyrotropin Suppression With Survival Outcomes in Patients With Intermediate- and High-Risk Differentiated Thyroid Cancer

Abstract: Key Points Question Is thyrotropin suppression associated with better outcomes in patients with intermediate- and high-risk differentiated thyroid cancer? Findings In this cohort study including 867 patients with intermediate- and high-risk differentiated thyroid cancer followed up for a mean (SD) of 7.2 (5.8) years, thyrotropin suppression was not associated with improved progression-free survival or overall survival. Meaning Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…Post-operative management of DTC involves administration of RAI [ 30 ], which has been shown to reduce both recurrence and death rates in DTC patients [ 31 ], and TSH suppression therapy, although data correlating TSH suppression with survival outcomes are equivocal [ 32 ]. Furthermore, in recent years, the new staging systems and prognostic tools suggested more conservative management of low- and intermediate-risk patients, indicating less extensive surgery and more use of RAI therapy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative management of DTC involves administration of RAI [ 30 ], which has been shown to reduce both recurrence and death rates in DTC patients [ 31 ], and TSH suppression therapy, although data correlating TSH suppression with survival outcomes are equivocal [ 32 ]. Furthermore, in recent years, the new staging systems and prognostic tools suggested more conservative management of low- and intermediate-risk patients, indicating less extensive surgery and more use of RAI therapy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the studies that demonstrated the effect of TST, many of them failed to show any impact of TST on the patients with low-risk DTC [11,13]. One study has recently reported that TST showed a limited benefit on prognosis even in the indeterminate- or high-risk DTC patients [16]. Therefore, in the era of emphasizing importance of a risk-adapted approach and individualized treatment, it is not appropriate to perform TST uniformly to all patients with low-risk DTC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review has concluded that TSH suppression in patients with intermediate-risk or high- risk differentiated thyroid cancers may be of limited benefit ( 34 ). It will be of interest and importance to determine whether this is a function of increased susceptibility of such tumors to T4-induction of radioresistance via integrin αvβ3.…”
Section: Thyrotropin (Tsh) Receptor and Integrin αVβ3mentioning
confidence: 99%